2011
DOI: 10.1614/wt-d-10-00140.1
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Atrazine as a Tank-Mix Partner with Tembotrione

Abstract: Manufacturers of several POST corn herbicides recommend tank-mixing their herbicides with atrazine to improve performance; however, future regulatory changes may place greater restrictions on atrazine use and limit its availability to growers. Our research objectives were to quantify the effects of tank-mixing atrazine with tembotrione compared to tembotrione alone on (1) weed control, (2) variability in weed control, and (3) sweet corn yield components and yield variability. Field studies were conducted for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
1
24
0
1
Order By: Relevance
“…14 and 28 d after POST (DAPOST)(Table 3). Similarly,Williams et al (2011) reported 77 to 95% control of giant ragweed in sweet corn with a tank-mixture of tembotrione and atrazine. A POST application of tembotrione plus atrazine was more effective for control of giant ragweed compared with a PRE application of isoxaflutole /thiencarbazone plus atrazine.…”
mentioning
confidence: 93%
“…14 and 28 d after POST (DAPOST)(Table 3). Similarly,Williams et al (2011) reported 77 to 95% control of giant ragweed in sweet corn with a tank-mixture of tembotrione and atrazine. A POST application of tembotrione plus atrazine was more effective for control of giant ragweed compared with a PRE application of isoxaflutole /thiencarbazone plus atrazine.…”
mentioning
confidence: 93%
“…Jhala et al (2014) also reported similar (96-98%) control of the same Palmer amaranth biotype from Nebraska with tembotrione applied alone or tank mixed with atrazine. In contrast, Stephenson et al (2015) and Williams et al (2011) reported 95 to 97% control of susceptible Palmer amaranth and redroot pigweed with tembotrione tank mixed with atrazine compared to tembotrione applied alone (80-91%). Palmer amaranth control was reduced at 28 DAT due to new seedling emergence because of its extended emergence pattern; therefore, tank-mixing atrazine with topramezone or tembotrione did not improve control compared to when applied alone at 28 DAT, with the exception of tank mixing topramezone at 22 g ha -1 with atrazine at 2240 g ha -1 .…”
Section: Tank Mixtures Of Photosystem Iiand Hppd-inhibitor Applied Pomentioning
confidence: 87%
“…The percentage of weed control, at 30 DAT, ranged from 77% (mesotrione: 0.072 + 0.5% oil) to 85% (atrazine + mesotrione: 1.25 + 0.072 + 0.5% oil). Williams et al (2011) emphasized the importance of using atrazine in a tank-mix with other herbicides due to the increase in spectrum of weed control. The authors observed that in tank mixing of atrazine with HPPD-inhibiting herbicides provided increases in the number and weight of ears of sweet corn of 9% and 13%, respectively, when compared to these herbicides applied alone.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%